Polyarthritis and erythema nodosum: an unusual presentation of tuberculosis - Gupta, Partisha; Dhanawat, Aditya; Mohanty, Lalatendu; Mishra, Siddhartha (International Journal of Advances in Medicine, 2019)
Reactive arthritis and erythema nodosum occur in presence of active tubercular infection and both are immunological phenomenon. Author described a case report of a 17year old female with 10months history of symmetrical polyarthritis and presence of healed lesions of erythema nodosum. She was also found to have caseating granulomatous lesion in right supraclavicular lymph node which led us to diagnosis of tuberculous lymphadenitis presenting as reactive polyarthritis (poncet’s disease) and erythema nodosum. Her joint pain and swelling dramatically resolved after 2weeks of ATT. Thus, tuberculosis may manifest as reactive polyarthritis (poncet’s disease) and erythema nodosum and they should be kept in mind even in the absence of other clinical clues of TB, to provide patients with a good clinical outcome.